2004
DOI: 10.1023/b:pham.0000016238.44452.f1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oral Absorption of Paclitaxel in a Novel Self-Microemulsifying Drug Delivery System with or Without Concomitant Use of P-Glycoprotein Inhibitors

Abstract: The results indicate that SMEDDS is a promising novel formulation to enhance the oral bioavailability of paclitaxel, especially when coadministered with a suitable P-gp inhibitor, such as CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 27 publications
3
86
0
3
Order By: Relevance
“…Other P-glycoprotein blockers that could also serve as CYP 450 inhibitors also boosted the oral absorption of paclitaxel Bardelmeijer et al, 2004;Choi & Li, 2005;Kim et al, 2004;. Formulations that do not contain Cremophor EL, that could lower the in vivo toxicity and increase solubilization of paclitaxel, were shown to deliver paclitaxel efficiently via oral administration especially when P-glycoprotein inhibitors were given simultaneously Gao et al, 2003;Yang et al, 2004;Woo et al, 2003;Choi et al, 2004aChoi et al, , 2004bPeltier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other P-glycoprotein blockers that could also serve as CYP 450 inhibitors also boosted the oral absorption of paclitaxel Bardelmeijer et al, 2004;Choi & Li, 2005;Kim et al, 2004;. Formulations that do not contain Cremophor EL, that could lower the in vivo toxicity and increase solubilization of paclitaxel, were shown to deliver paclitaxel efficiently via oral administration especially when P-glycoprotein inhibitors were given simultaneously Gao et al, 2003;Yang et al, 2004;Woo et al, 2003;Choi et al, 2004aChoi et al, , 2004bPeltier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2) Un tel profil a été décrit auparavant dans la littérature [24,36]. La demi-vie d'élimination du principe actif est de 4,5 h et le TRM de 2,6 h. Ces deux résultats concordent aussi avec des valeurs antérieurement décrites [16,22,23]. Quand le médicament commercial est administré par voie orale, les niveaux plasmatiques du paclitaxel sont inférieurs à la limite de détection de la technique analytique utilisée.…”
Section: Discussion Et Conclusionunclassified
“…Pour résoudre ce problème tout en promouvant la biodisponibilité orale du paclitaxel, le recours à plusieurs systèmes de délivrance de médicaments a été envisagé : micelles [21], systèmes autoemulsionables [22,23], nanoémulsions [24] et nanocapsules lipidiques [16]. De tels systèmes permettent, en général, l'association, à la formulation, d'inhibiteurs de la P-gp et du cytochrome P450, tels que la cyclosporine A [22] ou des flavonoïdes [25]. Le présent travail est consacré à la mise au point d'un système permettant l'administration du paclitaxel par voie orale.…”
Section: Introductionunclassified
“…Lipid formulations, such as self-microemulsifying drug delivery systems (SMEDDS) (Yang et al, 2004;Lo et al, 2010;Oostendorp et al, 2011) and lipid nanocapsules (LNC) (Peltier et al, 2006) have been reported to enhance the oral bioavailability of PTX. SMEDDS and LNC formulations of PTX have shown 2-fold and 3-fold higher oral bioavailability, respectively, compared to that of an orally administered Taxol formulation (Yang et al, 2004;Peltier et al, 2006). Mechanisms by which lipids improve the bioavailability of PTX may include enhanced solubilization of PTX in the gastrointestinal lumen and increased absorption via selective lymphatic uptake (Yang et al, 2004;Porter & et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SMEDDS and LNC formulations of PTX have shown 2-fold and 3-fold higher oral bioavailability, respectively, compared to that of an orally administered Taxol formulation (Yang et al, 2004;Peltier et al, 2006). Mechanisms by which lipids improve the bioavailability of PTX may include enhanced solubilization of PTX in the gastrointestinal lumen and increased absorption via selective lymphatic uptake (Yang et al, 2004;Porter & et al, 2007). Lipidbased formulations have been widely applied for highly lipophilic drugs to promote their intestinal lymphatic transport (Ling et al, 2006;Murota et al, 2013).…”
Section: Introductionmentioning
confidence: 99%